NORMALIZATION OF DIFFICULT LOAN PAYMENTS: A SEMIOTIC ANALYSIS OF LOAN SERVICE ADVERTISEMENT IN POST PANDEMIC ERA - Indrawan, Fani; Nastiti, Nimas Diah Putri Ayu Dewi (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2022)
This study focuses on semiotic analysis of Kredivo's commercial video entitled